KEPERCAYAAN MASYARAKAT TERHADAP DUKUN (Studi Kasus di Desa Pulau Komang kecamatan Sentajo Raya Kabupaten Kuantan Singingi) - Yusmarita "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Dukun are a place to solve problems, a place to ask for advice and opinions. A place to support the success and success they want. This study aims to analyze why people still trust the shaman and to analyze the meaning of the shaman for the community. The study was conducted in Pulau Komang Village, Sentajo Raya District, Kuantan Singingi. Data analysis in this study is qualitative descriptive analysis. The results of this research are that about 70% of the Komang Island community still believes in dukun because dukun can always help when asked for help, only dukuns are able to cure all kinds of illnesses and dukun can solve various problems or provide solutions. The meaning of the shaman for the community of Komang Island Village is a place to ask for help, cure all kinds of diseases and as an intermediary to resolve all problems. Keywords: Shaman, Trust, Relief